PROSES MORFOLOGIS BAHASA INDONESIA DALAM UNGGAHAN MEDIA SOSIAL INSTAGRAM ISBI SINGKAWANG (EDISI TAHUN 2021) - Diny Aprillya; Gunta Wirawan; Lili Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the forms of morphological processes of the Indonesian language found in the Instagram social media posts of ISBI Singkawang (2021 edition). The research method used is a descriptive method, and the form of this research is qualitative. The data sources consist of words, phrases, and clauses, which are then analyzed according to the types of morphological processes. The results of this study show the following morphological processes: (1) affixation, with 76 data findings; (2) reduplication, with 5 data findings; and (3) composition (compounding), with 4 data findings. This research can be implemented in Grade VIII as Indonesian language teaching material on the topic of Creating Advertisement Texts, Slogans, and Posters in the Merdeka Curriculum, specifically targeting the learning outcomes in the elements of writing and listening.